SUSTAINABLE FINANCIAL LITERACY POLICY IN BREAKING THE CHAIN OF DEBT AND RECEIVABLES IN HOUSEHOLDS - FADLI, AHMAD; MASRUROH, NIKMATUL; FAWAID, YAZIDUL; SHAHRIN, ATTORI ALFI (JEBI (Jurnal Ekonomi dan Bisnis Islam), 2024)
The purpose of this research, firstly; explore the practices of accounts payable and receivable that occur in households, secondly; the formulation a sustainable financial literacy policy through digital applications and cooperative innovation and changing "titil" banks into sharia-based "installment" banks. The method used in writing this work is literature review and netnography. This approach is used to explore data via the internet from various conversations on social media as well as observing phenomena that occur in society related to debt and receivable transactions. Data was obtained through library or literature studies. Data analysis uses interpretive analysis to interpret data related to policies in carrying out continued financial literacy. Main findings in this research, namely, there are various types of debt practices in Indonesian households, there are models of debt to bank and non-bank financial institutions, there are models of debt to banks "titil", models of debt to loan sharks, models of debt via online applications (pinjol), debt to fellow neighbors, debt through cooperatives, debt by participating in social gatherings and so on. Various variations of debt models exist in Indonesian households. The way to overcome this is by presenting an application-based literacy policy. So, you can prevent debts from piling up further.